Classes and contradictions in the capitalist city: foundations for historical specificity - Lorena, Elton Rafael (Pontifícia Universidade Católica de São Paulo, 2012)
This article attempts a theoretical first approximation to the problems related to the urbanquestion and its relationship to capitalist reality. Its objective is to underscore some pointsthat we believe to be of great relevance for the accurate understanding and analysis of theproblem of social classes and the structural contradictions of the capitalist urban environment.